Climate Change and Indian Grapes: Analyzing the Economic Impact on Export-Dependent Agriculture (2022-2023) - Madrewar, Shivam Satyawan; Shrishty, Apurva; Sathe, Snehal Netaji; Tavhare, Prathamesh Balasaheb; Suryawanshi, Om Vijay; Kulkarni, Bhakti Balavant (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
This study examines the impact of climate change on India's export-dependent grape industry, focusing on the 2022-23 season. The 2022-23 season was marked by climatic anomalies that adversely affected grape yields and quality, leading to substantial economic losses for both farmers and exporters.During the 2022-23 season, average temperatures in key grape-growing regions increased by 1.5°C above the long-term norm during critical growth periods. This temperature rise accelerated the ripening process, resulting in smaller berries with lower sugar content, which diminished fruit quality. Additionally, unseasonal rains in October 2022 and February 2023 exacerbated the situation by causing fungal diseases, waterlogging, and grape splitting, further compromising the crop. The study reveals a 12% decline in grape production in Maharashtra, with total production dropping from 2.8 million metric tons in 2021-22 to 2.5 million metric tons in 2022-23. This reduction was mirrored by a 15% decrease in grape export volumes, from 280,000 metric tons to 238,000 metric tons, and an 18% decline in export value, from USD 335 million to USD 275 million